Is loss beneficial? The role of assimilation in holistic thinking and meanings made - Thamran, Letisha (Nanyang Technological University, 2024)
Loss can be painful, but it may also offer people something they did not see before. Why can some people see new meanings after losing someone they love, and some cannot? What underlying processes are in operation? These questions are the focus of this research. We hypothesized that holistic thinking would facilitate meanings made from loss. We also hypothesized that assimilation would play a mediating role in the causal relations between holistic thinking and meanings made. Two studies examined these hypotheses with an experimental-causal-chain design. In a pilot study, we developed a novel manipulation of holistic thinking for Study 1 and validated meaning-related words for the meanings made measure in Study 2. Experimentally manipulating holistic thinking elicited assimilation of loss, reflected in a puzzle association task (Study 1). Inducing assimilation strengthened meanings made from the loss, reflected in a word fragment task (Study 2). These results were unexplained by alternative accounts such as age, gender, cultural background, religion, education (Study 1-2) or personality factors (Study 2). Together, these findings shed light on the causal relationship between holistic thinking and meanings made from loss, mediated by assimilation. By integrating insights from positive and cultural psychology, our research advances the understanding of how people seek meaning in times of stress. We discuss the implications of our findings and suggest avenues for future research.